Internet+ China: Unleashing the Innovative Nation Strategy - Keane, Michael (National Cheng Kung University, 2016)
From the time of their inception in 2001 China’s cultural industries were predominantly material, following the blueprint of industrialization (chanyehua) laid out in the national Five Year Economic Development Plans. A significant shift is now occurring, coincident with China’s most recent wave of economic transformation, influenced by the global policy movement known as The Third Industrial Revolution. This article investigates China’s aspirations to become an innovative creative nation focusing on specific implications of the government’s Internet+ policy within the 13th Five Year Economic Development Plan. It argues while a digital ecosystem is developing thanks to the relationship between government and China’s leading Internet companies, a number of challenges remain if China is to become an innovative creative nation. These include harnessing the creative talents of grassroots communities, dealing with the reality of an aging population, and finding a way to produce hybrid cultural products that the world market finds attractive. The borderless connectivity of the Internet, as well as the willingness of companies, both Chinese and Western, to compromise in the pursuit of profit promises a new dawn.